Mobile barcode system with Inventory management and Employee work tracking using Google Analytics (International Journal of Engineering and Computer Science, 2015)
The paper includes three aspects ,firstly we are going to replicate the commercial barcode scanner (i.e HC2D barcode andQR-code) on the mobile device which operates on Android. Secondly using this application in Inventory management and Employeework tracking. Thirdly using Google Analytics for product tracking, automatic report generation. Our main goal is to decode thebarcode images in real-time, quickly and efficiently. This involves improving the image decoding algorithms and choosing efficient imagemanipulation and barcode libraries .Here our focus is basically on implementing reader for HC2D barcode. The HC2D is a highcapacity two dimensional barcode. Barcode represents data using lines, rectangles and spacing between them. For reading the HC2Dbarcode, the bit representation of the barcode is obtained by scanning the image of the barcode with scanner machine only. A HC2Dbarcode is a 2D barcode which consists of a black square pattern on white background. The HC2D barcode contains information in thevertical direction as well as the horizontal direction. Here we propose a system to read a HC2D barcode in real time mode using theembedded camera device in mobile phones. The proposed system consist of algorithm to work on code area found by the 2 vertical line,one horizontal line and dash line detection of H2CD barcode. Thus our proposed system works in real time environment and eliminatesall the drawbacks of earlier systems.